Shiga toxin‐encoding genes (stx genes) in human faecal samples. Issue 3 (17th September 2012) - Urdahl, Anne Margrete; Solheim, Heidi Tetlie; Vold, Line; Hasseltvedt, Viggo; Wasteson, Yngvild
Abstract : The aim of the two studies reported here was to investigate the distribution of stx genes in human faecal samples from volunteers and in faecal samples submitted to a regional microbiology hospital laboratory, and to isolate and characterize STEC from stx ‐positive samples. In total, faecal samples from 13.9% of 165 volunteers and 36.1% of 416 swabs from the regional microbiology hospital laboratory were positive for stx genes after screening by PCR. Isolation of STEC and of E. coli O157 from stx ‐positive faecal samples was performed by a filter‐hybridization protocol and by automated immunomagnetic separation, respectively, and isolates were further characterized by serotyping, virulence typing by PCR and toxin production by the Vero cell assay. STEC were isolated from two samples only, an O146:H21 isolate from one of the volunteers and an O157:H7 isolate from a human case of diarrhoea. To conclude; the results show that it is not unusual to detect stx genes in faecal samples from humans in Norway, both from asymptomatic people and from people with gastrointestinal illness. This finding emphasizes the importance of correct diagnostic criteria for interpretation of the finding of an occasional stx ‐positive sample or an STEC isolate when searching for an aetiological agent of human cases of diarrhoea.